Feeding value of grass ensiled with absorbents assessed in growing lambs - Sormunen-Cristian, Riitta; Mannerkorpi, Päivi (Agricultural and Food Science, 1997)
Four absorbent materials incorporated into grass at ensiling were compared in terms of their effects on silage quality, effluent production, diet digestibility, ad libitum intake and growth of lambs. The materials used (50 kg t-1 grass) to retain silage effluent flow were molassed and unmolassed sugar beet shreds (MSBS, SBS), a commercial product (CP) based on MSBS (75%) and wheat bran (20%), and rolled barley (RB). With the exception of MSBS and a control (C2), all silages were ensiled with formic acid solution. Unmolassed sugar beet shreds were also ensiled with a granulated formic acid product (grFA). The silages were fed to 56 Finnish Landrace lambs for 21 days. Silage effluent retention rates were similar (1.44-1.55 kg kg-1 absorbent) for the sugar beet shred-based absorbents but zero for RB. The organic matter digestibilities of the diets were not affected (p>0.05) by the silage absorbent treatment. The digestibility of SBS silage was, however, improved by grFA as an additive. Silage intake was generally increased by absorbent inclusion, and was about 29% higher in lambs receiving silages treated with sugar beet shreds than in those receiving untreated silages. The daily growth rate of lambs was highest with the SBS treatment (124 g) followed by SBS ensiled with grFA (108 g) and MSBS (86 g); it was lowest with RB (36 g). With regard to effluent chemical oxygen demand, digestibility and silage intake, the use of SBS as an absorbent material is recommended by ensiling with either liquid or grFA.